EXCHANGES RATES, STOCK PRICES AND EARNING MANAGEMENT: EMPIRICAL EVIDENCE OF BLUE-CHIP COMPANIES IN SOUTHEAST ASIA - Sari, Martdian Ratna; Meliyanti, Meliyanti (Journal of Management and Business Review, 2019)
Stock price is an important part of fundings in a company. On the other hand, this component is very dependent on the macro situation of the company which will affect the management-decision-making. This reflects that management’s actions manage corporate earnings are not based on internal source but also from the external factors. This study discusses about external factors that can affect management’s action is the exchange rate. This research has a purpose to analyze the impact of exhange rate to earning management by using stock price as intervening variable. This research used secondary data. The population in this study are Top Asean Stars blue-chip companies from various industry sectors contained in Asean Exchanges 2015-2017. The population in this study comes from 3 ASEAN countries namely Indonesia, Malaysia and Singapore. The sample are selected using purposive sampling method and there are 161 companies that meet the criteria of the sample. The method used for earning management’s calculation is Modified Jones Model. This study used multiple linear regression methods and path analysis. The results showed that stock prices is not an intervening variable for exchanges rate on earning management.